Association of Thrombocytosis and its Prognostic Significance in Cervical Cancer - Sahithya Sivaprasad; SR Sheela (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Thrombocytosis is associated with progression of many diseases. There is increasing evidence that tumour cells, platelets, endothelial cells interact with each other leading to spread of tumour cells into the microvasculature which results in poor prognosis due to metastasis. Thrombocytosis is an indirect marker of occult advanced disease. Aim: To determine thrombocytosis in diagnosed carcinoma cervix patients and its association with stage of cancer cervix and prognosis. Materials and Methods: This was the retrospective study conducted at Sri Devaraj Urs Medical College, Kolar, Karnataka, India, from April 2021 to May 2022, on medical records of 52 patients who were diagnosed with cancer cervix. The data abstracted from each subject’s medical record include the following: age, parity, clinical staging as per International Federation of Gynaecology and Obstetrics (FIGO), size of the lesion, complete blood count and length of the survival. Patients underwent surgery followed by appropriate chemo-radiotherapy or brachytherapy. They were followed-up after treatment every three months for the first two years and every six months for the next three years and annually thereafter. The five-year survival rate of these patients who were on complete follow-up was analysed. The normal platelet count was considered as 4.5×109/L. Results: The mean age of the study population was 50.28 years. Among the 52 patients, 47 (90.03%) were with advanced stages of cancer cervix (stages IIB-IVB) and 5 (9.6%) belonged to early stages of cancer cervix (stages 1B-IIA). Forty patients (76.92%) had a platelet count less than 4.5×109/L, out of which 2 patients were in early stage of cervical cancer and 16 patients were with tumor size less than 4 cm. A total of 12 patients had the platelet count more than 4.5 lac. All these 12 patients belonged to advanced stages of cancer cervix (stage IIB-IVB), p-value of 0.001. Among the 12, 11 patients had a tumour size of more than 4 cm, p-value 0.040. The mean five-year survival rate among patients with advanced stages of cancer cervix associated with thrombocytosis was 18%. Conclusion: The platelet count was found to have strong association with the tumour size, stage of the cervical cancer and five year survival rate thus making thrombocytosis to be a strong prognostic factor in cancer cervix.